2012
DOI: 10.1038/jid.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Gene Gun Delivery of hNC16A Induces BPAG2-Specific Tolerance

Abstract: Immune recognition and rejection of tissues expressing transfected genes is a major complication of gene replacement therapy for inherited genetic disorders. Owing to the high immunogenicity of human bullous pemphigoid antigen 2 (hBPAG2), the induction and maintenance of tolerance to this neo-antigen is essential to deliver the gene product to patients with epidermolysis bullosa junctionalis. In a skin grafting mouse model, we used gene gun transfection with a construct encoding hNC16A, the immunodominant doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Although not further investigated, it is likely that ssmDCs have been the vehicle to induce myelin-specific Tregs in the skin-draining lymph nodes. Surprisingly, even approaches using gene gun delivery of antigens, that has been developed for immunogenic vaccines, may be used to induce stable tolerance by induction of Foxp3+ Tregs and this may occur through ssmDCs (Ettinger et al, 2012). …”
Section: Steady State Migratory Dcsmentioning
confidence: 99%
“…Although not further investigated, it is likely that ssmDCs have been the vehicle to induce myelin-specific Tregs in the skin-draining lymph nodes. Surprisingly, even approaches using gene gun delivery of antigens, that has been developed for immunogenic vaccines, may be used to induce stable tolerance by induction of Foxp3+ Tregs and this may occur through ssmDCs (Ettinger et al, 2012). …”
Section: Steady State Migratory Dcsmentioning
confidence: 99%
“…Ettinger et al . recently reported that transcutaneous gene gun delivery of hCOL17‐NC16A induced immune tolerance towards hCOL17, a neo‐antigen for wild‐type mice, in a Treg‐dependent manner. Antigen‐specific immunosuppressive effects by DNA vaccination have also been shown in ongoing autoimmune disease models such as experimental autoimmune encephalomyelitis and type 1 diabetes .…”
Section: Potential Therapeutic Strategies For Targeting Autoreactive mentioning
confidence: 99%
“…However, in relation to the antigens involved, it is possible to differentiate bullous, mucous membrane, gestationis and anti-p200 pemphigoid diseases as well as linear IgA dermatosis, epidermolysis bullosa acquisita and lichen planus pemphigoides [9]. In order to discover the molecular basis of new diseases, the genomic approach can disclose multiple protein and gene interactions that could heavily influence patient susceptibility; moreover, the application of gene replacement therapy for inherited genetic disorders seems to be a promising strategy [23,24].…”
Section: Discussionmentioning
confidence: 99%